Hubungan Diabetes Melitus Tipe 2 Berdasarkan Usia dan Jenis Kelamin Dengan Kejadian Covid-19 di RSUD Dr. Pirngadi Kota Medan - Sihite, Rubintang; Silitonga, Hendrika A; Tarigan, Juliyanti (Jurnal Kedokteran Methodist, 2022)
Background: Diabetes mellitus is a metabolic disease in which there is an inappropriate increase in blood glucose levels. DM disease is very susceptible to pathogens so that it becomes a risk factor for morbidity and mortality of various viral infections so that it can be linked between comorbid DMT2 and Covid-19. Methods: Results Based on the research, the Covid-19 patients with comorbid DMT2 disease were 56 samples from 56 people (100.0%). these patients aged 50-60 years as many as 37 people (66.1%). In terms of gender, it was found that the majority of the research sample were women as many as 31 people (55.4%). The relationship between DMT2 patients based on age with the incidence of Covid-19 using the Chi-Square test obtained a P value = 0.006 (< P = 0.05), there is a significant relationship between age in T2DM patients and the incidence of Covid-19. DMT2 patients based on gender with the incidence of Covid-19 from the Chi-Square test results obtained a P value = 0.013 (< P = 0.05), there is a significant relationship between gender and T2DM with the incidence of Covid-19. Results: Majority of the study samples who experienced type 2+ Covid-19 DM were aged > 30 years, namely 30 people (52.5%). The majority of the study samples with appendicitis were men, as many as 36 people (63.2%). The majority of the study samples experienced type 2 DM + Covid-19, namely 51 people (77.5%). Conclusion: Age has a significant relationship with the incidence of type 2+Covid-19 DM, where the older you get, the greater the risk of type 2+ Covid-19 DM (p=0.006 <0.05). Gender has a significant relationship with the incidence of type 2 DM + Covid-19, where men are more at risk of experiencing the incidence of type 2 DM + Covid-19 than women (p = 0.013 < 0.05).